Invariant manifold of hyperbolic-elliptic type for nonlinear wave equation - Xiaoping Yuan (International Journal of Mathematics and Mathematical Sciences)
It is shown that there are plenty of hyperbolic-elliptic invariant tori, thus quasiperiodic solutions for a class of nonlinear wave equations.